Implementasi Data Mining Untuk Prediksi Pola Penjualan Makanan Organik Menggunakan Algoritma Apriori - Rizki Gustianto Sidi; Dede Sahrul Bahri (OKTAL : Jurnal Ilmu Komputer dan Sains, 2023)
PT Indospirit Natura is engaged in the distribution of natural and organic food and beverages, headquartered in Kebon Jeruk, West Jakarta, and the distribution of its products has spread to various regions in Indonesia. So far, the use of sales transaction data at PT Indospirit Natura has only been stored as an archive. Even though the data can be utilized and processed into useful information for increasing product sales and product innovation. In this case, it is necessary to analyze the transaction data to obtain sales patterns. The result of this study is that the A priori Algorithm is able to be used to determine the products most often purchased by consumers by looking at the tendency of consumers to make transactions. The results of the analysis obtained after using the minimum support values of 30% (the strength of the combination of these items in the database) and the minimum confidence of 35% (the strength of the relationship between items in the association rules) resulted in twenty-eight association rules. One example is if consumers buy Bragg Acv 16 Oz, Bragg Seasoning 4.5 Oz And Bragg Olive Oil 473 Ml have a confidence value of 98.25% then it can be said that 98.25% of consumers who buy the Bragg Acv 16 Oz menu, Bragg Seasoning 4.5 Oz will also buy Bragg Olive Oil 473 Ml This information can make it easier to be used by PT Indospirit Natura in Predicting sales patterns.